THE GENESIS OF ELECTION CAMPAIGNS AND ELECTORAL TECHNOLOGY - Boltabaev Bakhtiyor Sabirjonovich (The Conference Hub, 2025)
This article will focus on the organization of election companies, the goals and objectives they set for themselves, the actions they carry out, their participation in competitive processes, the main feature of election technologies, the issue of socio-psychological mechanisms.
Keywords: election companies, sharp struggles between political opponents, modern election technologies, electoral strategy, campaign analytical information.